If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = 3(-4 + -5r) 63 = (-4 * 3 + -5r * 3) 63 = (-12 + -15r) Solving 63 = -12 + -15r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '15r' to each side of the equation. 63 + 15r = -12 + -15r + 15r Combine like terms: -15r + 15r = 0 63 + 15r = -12 + 0 63 + 15r = -12 Add '-63' to each side of the equation. 63 + -63 + 15r = -12 + -63 Combine like terms: 63 + -63 = 0 0 + 15r = -12 + -63 15r = -12 + -63 Combine like terms: -12 + -63 = -75 15r = -75 Divide each side by '15'. r = -5 Simplifying r = -5
| 36/7=144/x | | 4cos^20+6cosx+2=0 | | 14=2/3p=8 | | 83=-3x-5(2x-1) | | r(r-6)=7 | | 150=-6(4x-5) | | 4cos^2x-6cosx+2=0 | | (3-2i)+(-5+3i)=0 | | 289u^2-1=0 | | t^2-2t=3t+24 | | 8p+p^2=-16 | | -68=-4a-4(5-3a) | | 3x+11y-2=0 | | -16t^2+28t+6=0 | | -6(-2x+6)=-108 | | 10x+2=180-4x-4 | | 30x^2-120=-50x | | 4(a^2+18a+81)=120 | | ln(x^2+8)=6 | | E/-9=6 | | 125=5(5k-4) | | 1.05/1.26=x/.36 | | X=-3(4)+20 | | ln(-499.2)= | | -74=6+4(6m+4) | | 12t^2-164t-56=0 | | -25+15w=200 | | (.25x+3)=(.75x-7) | | (7x-5)/7 | | x/.36=1.05/1.26 | | (x1/2*x1/2)/x | | 4s-29=-23+6s |